Measuring childcare practices: approaches, indicators, and implications for programs - Ruel, Marie T.; Arimond, Mary (International Food Policy Research Institute, 2003)
The authors describe program measurement approaches, problems, and solutions for the assessment of child care practices. The review describes what is known and what is not known about how to improve our measurement of three types of child care practices: hygiene, child feeding and caregiver/child interactions during feeding:; Chapter 1 / Introduction; Chapter 2 / Background; Chapter 3 / Measurement of Hygiene Practices; Chapter 4 / Measurement of Child-Feeding Practices; Chapter 5 / Caregiver–Child Interactions during Feeding; Chapter 6 / Implications for the Measurement of Child Feeding, Hygiene, and Caregiver–Child Interactions in Program and Survey